تاريخ التعليم في الدولة المهدية في السودان: )1298-1315هـ / 1881- 1898م( - أسامة عبد الله محمد الأمين (White Nile Journal for Studies and Research, 2019)
This study deals with the history of education in Sudan during the Mahdia state of Sudan (1881 - 1898) following its different paths. The study aims at clarifying the role played by the Mahdist State in expanding the education in Sudan. The study followed the historical descriptive analytical method. In collecting historical scientific material the study used a number of sources and references that dealt with the subject of history of education in Sudan during the period of Mahdia State . The study reached several conclusions, the most significant is that, the Mahdia State is the first who introduced the experience of private education in Sudan .